Exploration of the Relationship between Management Talent, Work Behavior and Cultural Intelligence to Employee Work Innovation - Fadlan Maalip (Jurnal Sinar Edukasi, 2022)
This study aims to explore the relationship between talent management, work behavior, and cultural intelligence on employee innovation in the context of modern organizations. Employee innovation is an important element for organizational sustainability, especially in the era of globalization that demands high competitiveness. Talent management plays a strategic role in identifying, developing, and retaining individuals who have the potential to innovate. In addition, positive work behaviors, such as proactivity and collaboration, contribute to the creation of new ideas that have an impact on improving organizational performance. The results show that talent management, work behavior, and cultural intelligence significantly influence employee innovation, both individually and simultaneously.